Molecular Studies on Quinolone Resistant MDR E. coli Detected in Urine Specimens (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
Multidrug-resistant (MDR) Escherichia coli is a major cause of urinary tract infections (UTIs) and represents a growing public health concern due to its resistance to multiple antibiotics. This study aimed to investigate the prevalence of MDR E. coli in urine samples and to characterize the antibiotic resistance patterns and genetic mechanisms underlying resistance. A total of 40 urine samples were collected from patients at Mbarret El-Asafra Hospital in Egypt in 2021. Of these, 30 E. coli isolates were identified and tested for antibiotic susceptibility using the disk diffusion method across six antibiotics from four different classes. Molecular analysis was performed using polymerase chain reaction (PCR) to detect the presence of the parC gene, which is associated with quinolone resistance. Out of 30 E. coli isolates, 18 (60%) exhibited multidrug resistance. The majority of MDR isolates showed resistance to fluoroquinolones (levofloxacin and ciprofloxacin) and carbapenems (meropenem), with additional resistance observed against aminoglycosides and tetracycline. The parC gene was detected in 66.7% of MDR isolates, indicating a significant genetic basis for quinolone resistance. The resistance rates and presence of the parC gene were consistent with global trends, highlighting the widespread nature of antibiotic resistance among E. coli strains. The high prevalence of MDR E. coli in urine samples underscores the urgent need for enhanced antimicrobial stewardship and alternative treatment strategies. The detection of the parC gene in a substantial proportion of MDR isolates emphasizes the importance of molecular surveillance in understanding resistance mechanisms. These findings call for comprehensive approaches to mitigate the impact of MDR pathogens and ensure effective management of UTIs in clinical settings.
Keywords: Escherichia coli; Multidrug resistance; Urinary tract infections; parC gene; Antimicrobial stewardship